Risk of recurrence after chemoradiotherapy identified by multimodal MRI and 18F-FDG-PET/CT in locally advanced cervical cancer. (November 2022) - Skipar, Kjersti; Hompland, Tord; Lund, Kjersti Vassmo; Løndalen, Ayca; Malinen, Eirik; Kristensen, Gunnar B.; Lindemann, Kristina; Nakken, Esten S.; Bruheim, Kjersti; Lyng, Heidi
Highlights: In cervical cancer, multiparametric MR images were fused into hypoxia images. Imaging-based hypoxic fraction (HF) identified low-risk patients with 95% precision. Integration of MRI (HF) and FDG-PET (SUV) improved detection of high-risk patients. A candidate multimodal imaging biomarker, HF/SUV50, was defined. HF/SUV50 is based on standard diagnostic images and feasible in clinical practice. Abstract: Background and purpose: MRI, applying dynamic contrast-enhanced (DCE) and diffusion-weighted (DW) sequences, and 18F-fluorodeoxyglucose (18F-FDG) PET/CT provide information about tumor aggressiveness that is unexploited in treatment of locally advanced cervical cancer (LACC). We investigated the potential of a multimodal combination of imaging parameters for classifying patients according to their risk of recurrence. Materials and methods: Eighty-two LACC patients with diagnostic MRI and FDG-PET/CT, treated with chemoradiotherapy, were collected. Thirty-eight patients with MRI only were included for validation of MRI results. Endpoints were survival (disease-free, cancer-specific, overall) and tumor control (local, locoregional, distant). K trans, reflecting vascular function, apparent diffusion coefficient (ADC), reflecting cellularity, and standardized uptake value (SUV), reflecting glucose uptake, were extracted from DCE-MR, DW-MR and FDG-PET images, respectively. By applying an oxygen consumption and supply-based method, ADC and K trans parametric maps were voxel-wise combined into hypoxia images that were used to determine hypoxic fraction (HF). Results: HF showed a stronger association with outcome than the single modality parameters. This association was confirmed in the validation cohort. Low HF identified low-risk patients with 95% precision. Based on the 50th SUV-percentile (SUV50 ), patients with high HF were divided into an intermediate- and high-risk group with high and low SUV50, respectively. This defined a multimodality biomarker, HF/SUV50 . HF/SUV50 increased the precision of detecting high-risk patients from 41% (HF alone) to 57% and showed prognostic significance in multivariable analysis for all endpoints. Conclusion: Multimodal combination of MR- and FDG-PET/CT-images improves classification of LACC patients compared to single modality images and clinical factors.